2005
DOI: 10.1021/es051158s
|View full text |Cite
|
Sign up to set email alerts
|

Transient Performance of a Two-Phase Partitioning Bioscrubber Treating a Benzene-Contaminated Gas Stream

Abstract: The dynamic performance of a prototype, two-phase partitioning bioscrubber in response to fluctuating benzene waste gas feeds has been characterized through a series of spike, step, and shutdown-restart experiments. From stable operation at a nominal loading capacity of 62 +/- 6 g/(m3 h) and removal efficiencies of over 99%, the bioscrubber was subjected to influent benzene concentration step changes and spikes as high as 10- and 20-fold, respectively. The bioscrubber responded rapidly and effectively to all f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…In such a case, the presence of an organic phase has shown to be favourable as it will play a buffering role and avoid or, at least, reduce inhibition. 20,141 A similar effect will also be reached if an organic phase absorber is put in front of a conventional single aqueous phase stirred tank bioreactor, instead of directly mixing both the aqueous and the organic phase in the bioreactor itself. 139 Some typical examples of performance data for two-liquid phase stirred tank bioreactors are summarized in Table 6.…”
Section: Two-liquid Phase Suspended Growth Bioreactorsmentioning
confidence: 93%
See 1 more Smart Citation
“…In such a case, the presence of an organic phase has shown to be favourable as it will play a buffering role and avoid or, at least, reduce inhibition. 20,141 A similar effect will also be reached if an organic phase absorber is put in front of a conventional single aqueous phase stirred tank bioreactor, instead of directly mixing both the aqueous and the organic phase in the bioreactor itself. 139 Some typical examples of performance data for two-liquid phase stirred tank bioreactors are summarized in Table 6.…”
Section: Two-liquid Phase Suspended Growth Bioreactorsmentioning
confidence: 93%
“…20 It was observed that under given operating conditions the biomass concentration in the reactor will naturally reach and stabilize at a rather constant value. 140,141 Non-steady-state load conditions are not unusual in full-scale operation. In the case of occasional shock loads, the system may become inhibited and may need some time to recover in the case of a single aqueous phase bioreactor.…”
Section: Two-liquid Phase Suspended Growth Bioreactorsmentioning
confidence: 99%
“…1 However, the first design of this type of system required considerable operator intervention to maintain two distinct liquid phases and to operate the system at steady state. Design improvements led to the two-phase partitioning bioscrubber (TPPB) in which aqueous and organic phases are homogenously mixed, 6 and we have demonstrated the practical application of TPPB technology to the treatment of VOCs, in particular benzene, 3,7,8 with some publications directed to the demonstration of process feasibility 3,6,7 and others toward fundamental issues, such as maintenance energy and oxygen transfer. 7,9 Recently, TPPBs have also been applied to the treatment of other pollutants such as styrene, 10 isopropylbenzene, 11 dichloromethane, 12 pentachlorophenol, 13 n-hexane, 14 and mixtures of up to 11 compounds.…”
Section: Introductionmentioning
confidence: 99%
“…2 Of the biotechnologies used for the treatment of VOCs, biofiltration has been shown to be useful because of its uncomplicated and inexpensive design which is typically coupled with long-term performance requiring only minimal maintenance and operator attention. 3 However, biofilters have great difficulty in dealing with high inlet VOC concentrations because of the potential for microorganisms to be inhibited or killed at the biofilter inlet, 4 and are also prone to clogging and channeling.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficiency of biological method to remove water-insoluble VOCs is very low, mainly because the mass transfer from gas phase to liquid is blocked [4]. In the traditional biological method, the hydrophobic VOCs from the gas phase through the liquid membrane to biofilm exists greater resistance in the process of mass transfer, thereby reducing the bioavailability [5], and this has become the main factors of restricting the microbial capture and degradation of VOCs.…”
Section: Introductionmentioning
confidence: 99%